Effects of antibiotics on biofilm and unattached cells of a clinicalStaphylococcus aureusisolate from bone and joint infection. Issue 9 (September 2015) - Marquès, Claire; Tasse, Jason; Pracros, Anne; Collin, Valérie; Franceschi, Christine; Laurent, Frédéric; Chatellier, Sonia; Forestier, Christiane
Abstract : N/A: Treatment of orthopaedic infections remains challenging owing to the inability of antibiotics to eradicate biofilms and prevent their regrowth. The present study characterized the effects of 12 antibiotics on in vitro biofilm formed by a representative strain of meticillin‐susceptible Staphylococcus aureus (MSSA) isolated from a bone infection. Determination of the minimum biofilm eradication concentrations indicated that in vitro eradication of 24 h‐old biofilms required concentrations up to 51 200 times higher than MICs. The influence of the same panel of antibiotics was also investigated on biofilm formation at concentrations including the breakpoints, by numbering viable cells in the suspensions (individual cells) and the biofilm biomass. Except for fusidic acid, the presence of antibiotics during the initial steps of biofilm formation resulted in significant decreases in the number of sessile viable bacteria at the highest concentrations tested. Ceftarolin, daptomycin, fosfomycin, gentamicin, ofloxacin, rifampicin and vancomycin were the most effective drugs. Confocal microscopy analysis indicated that daptomycin was more efficient at bacteria lysis than gentamicin and vancomycin. However, viable individual cells were still detectable in the assays performed with ceftarolin, fosfomycin, ofloxacin, rifampicin and vancomycin at concentrations for which no sessile cells were detected. Although none of the molecules tested was effective at classical therapeutic concentrations against 24 h‐old MSSA biofilms, all except fusidic acid were able to impair biofilm formation at concentrations near the breakpoints. However, presence of viable individual unattached cells could imply a significant risk of microbial dissemination and increased risk of infections.